From De-escalation to Restraint: A Qualitative Study of Emergency Clinician Decision-Making in Patient Agitation - Michelle Suh; Beatrice Torres; Elise Brickhouse; Datonye Charles; Ynhi Thomas; Anita Chary (Western Journal of Emergency Medicine, 2026)
Introduction: Managing agitation in the emergency department (ED) is challenging and frequently involves decisions about physical restraints and emergent medications. While institutional protocols and behavioral response teams exist, little is known about how individual clinicians make decisions about restraint use—decisions with significant implications for safety, ethics, and equity. The objective of the study was to explore how emergency physicians, residents, and nurses make decisions about physical restraint and emergent medication use during episodes of patient agitation in the ED. Methods: We conducted a qualitative study using semi-structured interviews with 35 emergency clinicians (18 attending physicians, 7 senior residents, and 10 nurses) at an urban academic ED. Interviews were transcribed and analyzed using inductive thematic analysis. Results: Clinicians described three key factors informing restraint decision-making: (1) commitment to patient-centered care through noncoercive de-escalation; (2) real-time assessment of threats to staff and patient safety; and (3) team-based collaboration in both the restraint decision and implementation process. Participants shared a common mental model that prioritized verbal de-escalation before moving to pharmacologic or physical restraint. Clinicians acknowledged that unconscious bias and identity-based dynamics, including age, gender and race, may influence perceptions of threat and decision-making. Conclusion: Emergency clinicians share a consistent framework for managing patient agitation, suggesting potential for a standardized, team-based algorithm. Future interventions should consider clinician and patient identities, aiming to reduce disparities and enhance safety while minimizing restraint use.